Efektivitas Merdeka Belajar Kampus Merdeka (MBKM) bagi Mahasiswa Program Kampus Mengajar - Muchtar, Azmy Ali; Wahyudin, Yuyu; Niarrofah, Niarrofah; Muthiah, Salma (STAI Auliaurrasyidin Tembilahan, 2023)
State University of Malang (UNM) students who passed the MBKM program selection not only came from the geography education study program but also from other study programs. This will certainly be a new learning experience for them. The aim of the research is to find out whether there is effectiveness of MBKM for Campus Teaching program students after they graduate from the UNM campus. The research method used is descriptive quantitative. The sample in this study was 13 students who took part in the campus teaching program, which was all students who passed the campus teaching program at SMAN 2 Pare. Questionnaire data were analyzed using percentage techniques, while interview data were analyzed using reduction techniques. The results of questionnaires and interviews show that MBKM for Teaching Campus program students is effective after they graduate.